EXAMINATION OF THE CONFLICTS BETWEEN X AND Y GENERATIONS: RESEARCH FOR ACADEMICIANS - Nazan Yelkikalan; Sena Erden Ayhun (European Scientific Journal, ESJ, 2013)
Social, economic, politic and technologic recoveries caused changes in present structures of the culture of the societies. Behaviors of the generations born in different periods of time has been differentiated due to respective facts and brought conflicts along with it. Conflicts experienced by generations in social structure also made itself evident during the generations’ performances in organizations.Within this study, conflicts of the academicians partaking in X and Y generation categories and functioning in universities has been tried to be determined if they experienced conflicts between themselves. If conflicts were experienced, it is also examined that if said conflicts originated from relations, tasks and processes.Data are collected over the web sites by survey method, face to face meeting and via fax and 578 applicable interview results have been provided. The advantages of structural equation modeling, unidirectional variance analyses. As a result of the analyses made; it is reached to a finding that the academicians rarely experienced conflicts both with their generation and older or younger generations. Dependency of the conflicts experienced by the generations are explored due to relations, task and process conflicts and most intense felt conflict type has been expressed as task conflict.